International capital flow pressures and global factors - Linda S. Goldberg; Signe Krogstrup (Federal Reserve Bank of New York, 2023)
The risk sensitivity of international capital flow pressures is explored using a new Exchange Market Pressure index that combines pressures observed in exchange rate adjustments with model-based estimates of incipient pressures that are masked by foreign exchange interventions and policy rate adjustments. The sensitivity of capital flow pressures to risk sentiment, including for so-called safe-haven currencies, evolves over time, varies significantly across countries, and differs between normal times and extreme stress events. Across countries, risk sensitivities and safe-haven status are associated with selffulfilling exchange rate expectations and carry trade funding currencies. In contrast, association with more traditional macroeconomic country characteristics is weak.
Keywords: F32; G11; G20; 330; exchange market pressure; risk aversion; safe haven; capital flows; exchange rates; foreign exchange intervention; global financial cycle